ADAPTASI DAN NEGOSIASI PADA PERKAWINAN ORANG KOMERING BERDASAR PENDEKATAN STRUKTURAL FUNGSIONAL - Sani, Amilda (Siddhayatra, 2018)
Marriage in Indonesian is full of values and cultural rules that govern how marriages should be done. The marriage becomes the arena of conflict between individual or family interests. This paper will look at how these interests generate the various variants of marriage owned by the Komering community in the Cempaka and Batu areas. The adaptation and negotiation resulted the model of the wedding: (1) rasan tuha elder gawi, (2) rasan tuha takad padang, (3) ngakuk anak, and (4) sibambangan. This variant model of marriage is result of adaptation and negotiation between the right of the parent do determine the mate for her child, the parent's right to set the money request and dowry as a form of parental consent to her child's mate.